PERSEPSI MAHASISWA AKUNTANSI TERHADAP AKUNTABILITAS DAN TRANSPARANSI KEUANGAN PARTAI POLITIK - Kholmi, Masiyah (Faculty of Economics and Business, University of Muhammadiyah Malang, 2010)
The objectives of this research to know in the perceptions of the accounting students and post graduate on accountability and transparency toward the financial in political party. The uses descriptions study method approach. The result of the research are: 1. The accounting students and post graduate have to this similar view on accountability and transparency toward the financial in political party; 2. Financial accountability and transparency in political party is low.